Zinc-Arbuscular Mycorrhizal Interactions: Effect on Nutrient Pool, Enzymatic Antioxidants, and Osmolyte Synthesis in Pigeonpea Nodules Subjected to Cd Stress. Issue 14 (6th August 2017) - Kaur, Harmanjit; Garg, Neera
ABSTRACT: The intent of the experiments was to analyze impact of cadmium (Cd) and/or zinc (Zn) on membrane functionality, nutrient acquisition, antioxidant defense, and osmolyte accumulation in nodules of two pigeonpea ( Cajanus cajan (L.) Millsp.) genotypes (Sel 85N and P792) with and without arbuscular mycorrhizal (AM) fungus Funneliformis mosseae . Findings demonstrated that accumulation of Cd and Zn in nodules resulted in membrane destabilization, nutrient imbalance, increased antioxidant enzyme activities [superoxide dismutase (SOD), catalase (CAT), peroxidase (POX), and glutathione reductase (GR)], and osmoprotectants such as total free amino acids (FAA), total soluble sugars (TSS), proline, and glycine betaine (GB). Cd had higher negative effects than Zn. P792 was comparatively more metal sensitive and displayed higher reductions than Sel 85N. Application of Zn decreased Cd uptake and reduced the phytotoxic effects of Cd. Zn1000 in combination with F. mosseae restored nodular membrane stability; enhanced nutrient pool [phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), and iron (Fe)]; and boosted antioxidant enzyme activities and osmolyte synthesis in a genotype-dependent manner.